SOFTWARE DE PREDICCIÓN DEL NIVEL DE MONÓXIDO DE CARBONO (CO) DEL AIRE EN LA UNIVERSIDAD LIBRE SEDE BOSQUE - Jaime Alfonso Lemus Casas; Ricardo Andres Santa Quintero (Revista Ingeniería, Matemáticas y Ciencias de la Información)
This article presents the complete panorama of the project that allows to measure the air quality by means of measurementstations that the local government has arranged and by means of CANSAT devices that are self-constructed picosatellitethat, due to their low cost, can be placed directly in the places where you want to measure the impact of pollution. Thesetwo mechanisms for obtaining environmental data provide a large amount of data that must be stored, processed, andvalidated before being used by the algorithms that generate predictions of carbon monoxide levels. The strongestproblems of elevated levels of carbon monoxide in living organisms are described and it provides not only themeasurements, but also the predictions for each monitored area in the surroundings of the Universidad Libre, El Bosqueheadquarters.